Imaging and Clinicopathological Features of Acinar Cell Carcinoma - Qu, Qianqian; Xin, Yinghui; Xu, Yifan; Yuan, Yao; Deng, Kai (Frontiers in Oncology, 2022)
Background: Acinar cell carcinoma (ACC) is a rare pancreatic epithelial malignancy that poses a significant threat. However, there are few related clinical studies. The present study aimed to analyze the imaging and pathological features of ACC to provide a reference for better diagnosis and treatment planning. Methods: Thirty-nine with ACC, referred to Qianfoshan Hospital, Qilu Hospital and Provincial Hospital in Shandong Province from December 2012 to December 2020, were enrolled. Their imaging and clinicopathological features were analyzed. They were followed up for 1 year, and Cox regression was used to analyze the factors affecting patient prognosis. Results: ACC was more common in the middle-aged and elderly and peaked at approximately 60 years. The clinical manifestations of the patients were mostly flatulence and upper abdomen pain. The tumor was located in the head of the pancreas in 19 cases, with an average size of 5.8 cm. We found nerve invasion and liver metastasis in one case each. 8 patients showed irregular amorphous tumor calcification on plain computed tomography and 5 showed high and low signals on T1- and T2-weighted images, respectively. Immunohistochemistry revealed 100.0% positive rates for CK, β-catenin, and Ki-67. Thirty-three patients underwent surgical resection, and the 2-year overall mortality rate was 25.6%. Cox analysis revealed that smoking was an independent risk factor affecting patient prognosis. Conclusion: An in-depth understanding of the imaging and clinicopathological features of ACC is conducive to better diagnosis and treatment planning for ACC and subsequent improvement in patient prognosis.